Insights on CEFR and Its Implementation in Arabic Language Learning at Pesantren - Syani Amrulloh, Friendis (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
The Common European Framework of Reference (CEFR) provides guidelines for Arabic language teaching aids and curriculum development in language courses. The research investigated pre-service Arabic teachers' perceptions of CEFR in the context of the Mambaus Sholihin Islamic Boarding School. A total of 200 fourth- and fifth-year preservice Arabic teachers participated in the study. A mixed method design was used to collect data through a seven-point Likert scale questionnaire and semi-structured interviews. The quantitative findings revealed that the participants had a high level of understanding of the CEFR, particularly in the domain of assessment and the development of reference level descriptions. In contrast, qualitative data revealed that Mambaus Sholihin Islamic Boarding School preservice teachers had little knowledge of the CEFR, and their understanding of the CEFR was very limited. However, the pre-service teacher of the Mambaus Sholihin Islamic Boarding School expressed a positive view regarding the application of CEFR into classroom practice. Overall, these findings suggest that pre-service Arabic teachers have a poor understanding of the conception of the CEFR, suggesting that stakeholders of the Mambaus Sholihin Islamic Boarding School should raise awareness regarding the proper implementation of the CEFR and its alignment with the national curriculum